Analisis pengaruh Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor terhadap Pendapatan Asli Daerah di Provinsi Jawa Timur tahun 2013 - 2019 - Nimas Galuh Savitri; Ary Yunita Anggraeni (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2021)
This study aims to prove whether the Motor Vehicle Tax (PKB) and Motor Vehicle Transfer Fees (BBNKB) have an effect on Regional Original Revenue (PAD) at the Regional Revenue Agency of East Java Province. The data used in this study is the realization of Motor Vehicle Tax (PKB) and the realization of Motor Vehicle Name Transfer (BBNKB) as well as the realization of Regional Original Income at the Regional Revenue Agency of East Java Province in 2013-2019. In this study the test model used was linear regression. multiple. The results of this study are the motor vehicle tax variable has a significant effect on regional original income and the transfer fee for motorized vehicles has no significant effect on regional original income.